# Calculus

posted by .

I have trouble finding the second derivative, my answer is a little off from the answer key.
f(x)=(log(base2)x)^5
f'(x)=[5(log(base2)x)^4]/xln2
f"(x)=[20(log(base2)x)³(xln2)-(ln2+(x/2))(5(log(base2)x)^4)]/[x²(ln2)²]

for the f"(x), is g(x)=xln2? It is a product so I think it should be dealt with differently, but I am unclear on that.

Thanks

• Calculus -

in your f ''(x) you forgot to differentiate the log2x part , and in the second part when you differentiate xln2 you simply get ln2.
Remember ln2 is just a number so xln2 is (ln2)x , a simple term like 6x.

f ''(x) = [20(log(base2)x)³(1/(xln2)(xln2)-(ln2))(5(log(base2)x)^4)]/[x²(ln2)²]

Now doesn't the xln2 at the top and bottom of the first section cancel?
check my arithmetic, too early in the morning

• Calculus -

I have the same thing now, thanks! I thought I had to use product rule for xln2, but there's no variable in ln2, so it is accounted for a constant?

## Similar Questions

1. ### Math 12

7. Simplify. b) log base2 20 + log base3 8 + log base2 3 + log base3 4 I can't remember how to switch bases... Thanks!
2. ### Pre-Cal

log base2 5 square root of 512 use the definition of b^1/n log base2 512^1/5 Not quite sure what to do after this Simplfiy.
3. ### Algebra 2

How would I solve the equation: log(base2)4 - log(base2)(x+3) = log(base2)8 ?
4. ### Algebra 2

solve the equation: log(base2)^(x-3)log(base2)^5 = 2log(base2)^10 I don't know how to solve it, can someone help me?
5. ### Calculus

Find the second derivative of the following function: y=log(base2)x/x² y'=[(x/ln2)-2xlog(base2)x]/x^4 the derivative of x/ln2 is (ln2)^-1?
6. ### Math

Evaluate log(base2)8-log(base2)12+log(base2)6
7. ### Precalculus-Verify

log(base2)x-log(base2)6= log(base2)5+ 2log(base2)3 log(x/6)=3log15 (x/6)=15^3 6*(x/6)=15^3*6 x=15^3*6 =20,250 Answer is 270.... What did I do wrong...
8. ### Algebra

In the logarithmic expression . . . log(base 4) 8 , how does the base 4 become base 2?
9. ### Advanced Functions/ Precalculus Log

1. Evaluate 4^(log base4 64) + 10^(log100) 2. Write 1+log(base2)x^3 as a single logarithm 3. Write log(base b)√(x^3 y z^6) 4. Solve log(base 2)x-log(base 2)6=log(base 2)5+2log(base 2)3 5. Solve 3^(2x) = 9(81^x) 6. Solve 3^(2x)=7^(3x-1). …
10. ### math

Given that 2 log base2 (x+15) - log base2 x = 6 1.Show that x^2 -34x +225 = 0 2. Hence or otherwise solve the equation 2 log base 2 (x+15) - log base 2 x =6

More Similar Questions